AN ANALYSIS OF PLANT BLINDNESS IN TURKISH TEXTBOOKS USED AT THE BASIC EDUCATION LEVEL - Ahi, Berat; Atasoy, Volkan; Balci, Sibel (Scientia Socialis Ltd, 2018)
The importance of plants is not as clearly understood as that of animals. This lack of attention is called “plant blindness” and is considered one of the most important problems in biology education. Textbooks do not put much emphasis on plants and, therefore, they may contribute to plant blindness. In this research, ten textbooks used for teaching at the basic education level in Turkey were analyzed for plant blindness using the document analysis method. The words and photographs associated with plants and animals were analyzed. The data analysis did not find any evidence that could lead to a conclusion of plant blindness based on the text and photos of these textbooks. However, if the number of plant and animal species covered is increased, and more words and photos are used to introduce these species, children will become more familiar with plants and animals. Besides textbooks, other educational tools can be analyzed in terms of plant blindness to expand on the related literature. Keywords: plant blindness, photograph in textbook, document analysis, written text.
Keywords: Education & Educational Research; 4. Education